PENINGKATAN KUALITAS LAYANAN KONSUMEN PADA RADIO RADIO DAKWAH ISLAMIAH 100,5 FM - Setiawan, Arif Agung (Department of Management, 2015)
The purpose of this study was to determine the quality of service on 100.5 FM Radio Dakwah Islamiah, to know what service attributes less value performance and find out what attributes can be developed as a new added value, and to identify targets and priority repairs to be carried out by RDI 100.5 FM. The analysis tool used is Quality Function Deployment (QFD) by means House of Quality (HOQ) to convert the customer's voice directly to the technical requirements of the services produced. This study uses six operational variables, namely quality management, design of products and services, layout, location, process design and capacity, human resources in the job design attributes translate what the customer needs. The results of analysis shown that the quality of existing services in RDI 100.5 FM that is pretty good, but need repair and upgrading to meet the expectations of listeners is on the attributes of the hospitality crew, modulation radio announcer voice clarity. It is also shown to attribute that has a value that is less performance such as signal coverage, the number of pauses, specialization of employees, and knowable steps can companies do to improve the quality of service that has been sorted based on targets and priorities.